Biohybrid Circuits: Biofunctionalized Materials Featuring Feedforward and Feedback Circuits Exemplified by the Detection of Botulinum Toxin A (Adv. Sci. 4/2019). Issue 4 (20th February 2019) - Wagner, Hanna J.; Kemmer, Svenja; Engesser, Raphael; Timmer, Jens; Weber, Wilfried
Abstract : In article number1801320, Wilfried Weber and co‐workers present the incorporation of biological circuits into polymer materials capable of sensing and processing an input stimulus and producing a quantitative output. Positive feedback and/or feedforward network topologies detect the proteolytic activity of botulinum toxin A with adjustable kinetics and dynamic range. Image credit: Jo Richers (www.jorichers.com ).